Ultraman. 2, You're begging for the truth, but now you've seen too much - Shimizu, Eiichi, 1978-; Shimoguchi, Tomohiro, 1978-; Stan!, 1964- (Viz signature., 2015)
"With the SSSP now operating as a covert agency, Shinjiro Hayata has inherited the mantle of Ultraman from his father and learned of a new and terrifying alien invasion. Though Shinjiro has his father's powers and an amazing armored exo-suit, he has a lot to learn if he's going to survive this secret war!" --